The Endocrine Disruption of Prenatal Phthalate Exposure in Mother and Offspring - Qian, Yiyu; Shao, Hailing; Ying, Xinxin; Huang, Wenle; Hua, Ying (Frontiers in Public Health, 2020)
Phthalates are a group of ubiquitous synthetic endocrine-disrupting chemicals. Fetal and neonatal periods are particularly susceptible to endocrine disorders, which prenatal exposure to phthalates causes. There is increasing evidence concerning the potential endocrine disrupting for phthalate exposure during pregnancy. This article aims to review the endocrine impairment and potential outcomes of prenatal phthalate exposure. Prenatal exposure phthalates would disrupt the levels of thyroid, sex hormone, and 25-hydroxyvitamin D in pregnant women or offspring, which results in preterm birth, preeclampsia, maternal glucose disorders, infant cryptorchidism, infant hypospadias, and shorter anogenital distance in newborns, as well as growth restriction not only in infants but also in early adolescence and childhood. The relationship of prenatal phthalate exposure with maternal and neonatal outcomes in human beings was often sex-specific associations. Because of the potentially harmful influence of prenatal phthalate exposure, steps should be taken to prevent or reduce phthalate exposure during pregnancy.